Ataxia telangiectasia mutated inhibitor-loaded copper sulfide nanoparticles for low-temperature photothermal therapy of hepatocellular carcinoma. (June 2021) - Cai, Hongqiao; Dai, Xinlun; Guo, Xingren; Zhang, Lingxiao; Cao, Kunxia; Yan, Fei; Ji, Bai; Liu, Yahui
Abstract: Hepatocellular carcinoma (HCC) is the most frequent type of primary liver cancer, and is ranked the sixth most common neoplasm and the third leading cause of cancer-related deaths. Photothermal therapy (PTT) for thermal ablation of local tumors has recently emerged as a therapeutic strategy. However, the relatively high temperature of over 50 °C may lead to unexpected heat-related damage to tumor-adjacent normal tissues. Herein, we designed and synthesized ataxia telangiectasia mutated (ATM) inhibitor loaded hollow-structured CuS NPs with surface modification with anti-TGF-β antibody (CuS-ATMi@TGF-β NPs). CuS-ATMi@TGF-β NPs are highly photo-stable, can release encapsulated drugs, and increase the temperature to an effective level in a near-infrared (NIR)-responsive manner. Moreover, CuS-ATMi@TGF-β NPs specifically target tumors and thereby significantly inhibit tumor growth on contribution to synergistic low-temperature PTT and chemotherapy. This system not only achieved low-temperature PTT but also resulted in reduced damage to normal tissues. Modification with anti-TGF-β antibody enhanced target specificity and immune activation. The combination of PTT and ATM inhibitor showed synergistic effects and significantly attenuated the growth of the HCC via down regulation of heat shock protein (HSP). CuS-ATMi@TGF-β NPs are a highly promising platform for targeted tumor ablation via hyperthermia-mediated tumor death with minimal damage to normal tissues at a low temperature. Statement of significance: We constructed ataxia telangiectasia mutated (ATM) inhibitor-loaded hollow-structured CuS NPs with surface modification with anti-TGF-β antibody (CuS-ATMi@TGF-β NPs). CuS-ATMi@TGF-β NPs not only achieved low-temperature photothermal therapy (PTT) but also resulted in reduced damage to normal tissues and sufficient biocompatibility. The modification with anti-TGF-β antibody enhanced targeted specificity, cell endocytosis, and immune activation. In addition, the combination of PTT and ATM inhibitor synergistically attenuated the growth of the HCC via downregulation of heat shock protein (HSP). This study provided proof-of-concept for the ATM inhibitor that mediated low-temperature PTT with a potential for future clinical applications. Graphical abstract: Image, graphical abstract